Oyu Tolgoi underground: mine production modelling of a coupled material handling system - Isabel, A.; Olonbayar, U.; de Hennin, S.; McKenna, L.; Cuthbert, B. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The Oyu Tolgoi underground mine has a coupled material handling system that is comprised of multiple fixed plant machinery and heavy mobile equipment that aims to minimise delays using an integrated asset management calendar. Realising throughput across the coupled value chain to ensure that forecasting accurately reflects operations offers its challenges to the mine planning process. Throughput forecasting focuses on 2 primary crushers located approximately 1,300 m below the Gobi Desert, which feed either a conveyor system or a shaft hoist to surface. Ore is sourced from multiple production panels, with Panel 0 currently in steady-state production and Panel 2 North in ramp-up, while additional panels are under development. Each panel comprises hundreds of drawpoints that are mucked by loaders into orepasses. Material flows through truck chutes where road trains are loaded. The trucks then haul the ore to one of the 2 primary crushers. The material handling system is tightly coupled, comprising a combination of parallel and series components whose individual capacities collectively govern overall system performance. Each link in the chain is subject to specific capacity constraints that directly influence system throughput. The cave systems themselves impose additional operating rules and objectives, including panel-specific draw control and cave draw strategies. As production ramps up through the ongoing construction and commissioning of additional drawpoints, the actual throughput performance of each system component is statistically evaluated to inform planning and forecasting input parameters. This paper outlines the structured process used to identify and map system connections and constraints, integrate maintenance calendars, apply time usage models for each sub system, and develop schedules that are compliant with the governing cave rules and draw strategies for each panel.